2002
DOI: 10.1161/hc1102.105258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cariporide and Losartan on Hypertrophy, Calcium Transients, Contractility, and Gene Expression in Congestive Heart Failure

Abstract: Background-The purpose of this study was to compare long-term effects of cariporide with those of losartan in postinfarction heart failure. Methods and Results-Female Sprague-Dawley rats with large myocardial infarctions and sham controls were randomized to losartan, cariporide, or placebo after 7 days and treated for 49 days. Cardiac function was assessed by echocardiography and measurement of left ventricular pressures, and gene expression was assessed by competitive reverse transcription-polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…Aerobic interval training (AIT) involving periods at 90% of V O 2peak has been shown to rescue impaired cardiomyocyte contractility, attenuate myocardial hypertrophy, and reduce myocardial expression of atrial natriuretic peptide in a rat model of postinfarction heart failure. 9 The beneficial effects on cardiac remodeling and myocyte function were similar to those observed with the angiotensin II receptor blocker losartan, 10 which indicates that AIT might be a potent modifier of postinfarction heart failure. We therefore hypothesized that AIT is more effective than moderate continuous training (MCT) in enhancing cardiovascular fitness and reversing myocardial remodeling in patients undergoing optimal treatment for stable heart failure after a myocardial infarction.…”
Section: Editorial P 3042 Clinical Perspective P 3094mentioning
confidence: 69%
“…Aerobic interval training (AIT) involving periods at 90% of V O 2peak has been shown to rescue impaired cardiomyocyte contractility, attenuate myocardial hypertrophy, and reduce myocardial expression of atrial natriuretic peptide in a rat model of postinfarction heart failure. 9 The beneficial effects on cardiac remodeling and myocyte function were similar to those observed with the angiotensin II receptor blocker losartan, 10 which indicates that AIT might be a potent modifier of postinfarction heart failure. We therefore hypothesized that AIT is more effective than moderate continuous training (MCT) in enhancing cardiovascular fitness and reversing myocardial remodeling in patients undergoing optimal treatment for stable heart failure after a myocardial infarction.…”
Section: Editorial P 3042 Clinical Perspective P 3094mentioning
confidence: 69%
“…Two-dimensional color-flow Doppler in the parasternal long-axis and apical views was used to visualize valvular regurgitation, which was confirmed by continuous-wave Doppler recordings. [22][23][24][25] Treatment group identity was unknown during echocardiography.…”
Section: Echocardiographymentioning
confidence: 99%
“…This sodium overload could consequently lead to a calcium overload due to the increased activity of the sodium-calcium exchanger (NCX) (Chahine et al 2005;Baartscheer et al 2008). Studies using animal models of HF (Yoshida and Karmazyn 2000;Engelhardt et al 2002;Loennechen et al 2002;Chen et al 2004;Baartscheer et al 2008;Karmazyn et al 2008) as well as isolated cardiomyocytes (Karmazyn et al 2003) have demonstrated the beneficial effect of NHE-1 blockade in preventing cardiac hypertrophy. In addition, the levels of angiotensin II (Ang II), which is a hypertrophic factor and an indirect activator of NHE-1 (Karmazyn 2001), were elevated during the development of HF (Nakamura et al 1994).…”
Section: Introductionmentioning
confidence: 99%